Accountability and integrity in private food safety regulation: Evidence from the Australian food sector. Issue 1 (2nd November 2020) - Daugbjerg, Carsten
Abstract: With the proliferation of private regulation of food safety, governments have shown interests in engaging private schemes as co‐regulators. This raises the issue of accountability in private schemes; that is holding the bodies auditing the standards accountable. The ability to do so affects the integrity of private regulatory schemes. Holding auditors accountable can be conceived of as a principal–agent problem. This article analyses the two most widely used global private food safety standard schemes in the Australian food sector. The analysis shows that the existence of well‐developed accountability mechanisms and multiple principals has resulted in a multi‐layered and comprehensive system of accountability. Hence, holding auditors accountable to their principals does not appear to be a concern for governments considering to engage in co‐regulatory arrangements with private schemes. However, concerns about integrity have been raised. The prescriptive nature of the standards and the multitude of standard schemes with their own accountability arrangements has brought about a situation in which the individual auditors have to devote disproportionately much time to respond to the accountability mechanisms. Abstract : Private regulation has proliferated in the food sector in order to manage food safety. Holding auditors accountable within the private standard schemes is important for their integrity. The article shows that the existence of multiple principals has resulted in a comprehensive system of multiple accountability, but some integrity issues remain